The Interpretation of Tropical Architecture in Designing Nature School in Balige - Marsellyna Br Marpaung; Morida Siagian (International Journal of Mechanical, Industrial and Control Systems Engineering, 2024)
Conservation of natural resources and the environment is a global issue that needs serious attention and handling because there are many environmental problems. This is due to the lack of awareness of the younger generation about the environment. Balige is the capital of Toba Regency which is an area that has considerable natural wealth and potential. However, the natural wealth owned has not been utilized optimally. Therefore, there is a need for follow-up in the form of establishing a Nature School which is capable of educating today's young generation to increase their awareness of the environment and make the most of it. This Nature School is planned to be located in the Soposurung area with consideration of a suitable location for developing an educational zone. This building applies sustainable architecture that makes the most of the potential of the surrounding environment.